Apakah Asupan Natrium Berlebih Merupakan Faktor Risiko Overweight?: Tinjauan Sistematis: Is Excess Sodium Intake a Risk Factor for Overweight?: A Systematic Review - Annisaa Wulida Furqonia; Farapti Farapti; Hari Basuki Notobroto (Amerta Nutrition, 2023)
Background: World salt consumption exceeds 200% of the daily recommendation. Obesity is the third largest health problem in the world. Various studies have begun to explore potential association mechanisms between sodium intake and weight gain, the risk of being overweight, and obesity. Objective: To analyze the relationship between sodium intake and the risk of being overweight regarding nutritional status, central obesity, and body composition in the adult population. Methods: This research was a systematic review. The data collection process used Pubmed and Science Direct databases with the keywords “obese” OR “overweight” OR “adiposity” AND “sodium” OR “salt intake” AND “adult.” Articles were selected through title and abstract, which were re-selected according to inclusion and exclusion criteria. Discussion: There are 11 kinds of literature related to nutritional status, 10 to central obesity, and 3 to body composition. Sodium intake was associated with an increase in body weight and the risk of being overweight, an increase in body weight of up to 2.75 kg, an increase in waist circumference of up to 2.15 cm, and an increase in fat mass up to 0.91 kg. Potential mechanisms underlying this relationship include energy intake, increased extracellular volume, increased adiposity, and changes in plasma leptin. Conclusion: There is a relationship between excessive salt consumption and increased body weight and risk factors for being overweight regarding nutritional status, central obesity, and body composition in the adult population. However, the mechanism of this relationship still needs to be studied further.